Processing of Self versus Non-Self in Alzheimer’s Disease - Bond, Rebecca L.; Downey, Laura E.; Weston, Philip S. J.; Slattery, Catherine F.; Clark, Camilla N.; Macpherson, Kirsty; Mummery, Catherine J.; Warren, Jason D. (Frontiers in Human Neuroscience, 2016)
Despite considerable evidence for abnormalities of self-awareness in Alzheimer’s disease (AD), the cognitive mechanisms of altered self-processing in AD have not been fully defined. Here we addressed this issue in a detailed analysis of self/non-self-processing in three patients with AD. We designed a novel neuropsychological battery comprising tests of tactile body schema coding, attribution of tactile events to self versus external agents, and memory for self- versus non-self-generated vocal information, administered in conjunction with a daily life measure of self/non-self-processing (the Interpersonal Reactivity Index). Three male AD patients (aged 54 to 68 years; one with a pathogenic mutation in the Presenilin 1 gene, one with a pathogenic mutation in the Amyloid Precursor Protein gene, and one with a CSF protein profile supporting underlying AD pathology) were studied in relation to a group of eight healthy older male individuals (aged 58 to 74 years). Compared to healthy controls, all patients had relatively intact tactile body schema processing. In contrast, all patients showed impaired memory for words previously presented using the patient’s own voice whereas memory for words presented in other voices was less consistently affected. Two patients showed increased levels of emotional contagion and reduced perspective taking on the Interpersonal Reactivity Index. Our findings suggest that AD may be associated with deficient self /non-self differentiation over time despite a relatively intact body image: this profile of altered self-processing contrasts with the deficit of tactile body schema previously described in frontotemporal dementia associated with C9orf72 mutations. We present these findings as a preliminary rationale to direct future systematic study in larger patient cohorts.